Winning the loser's game : timeless strategies for successful investing - Ellis, Charles D. (New York : McGraw Hill Education, 2021)
"One of the most respected and revered names on Wall Street, Charles Ellis updates his influential work to reflect the new realities of today's markets Technology, information overload, and increasing market dominance by expert investors and computers are making it harder than ever for active managers to produce results that overcome operating costs and fees. Winning the Loser's Game shows investors how to index to reduce costs, fees, and taxes, and focus on long-term policies that are right for them. Candid, short, and super easy to read, Winning the Loser's Game provides everything investors need to create a powerful investing strategy that generates solid profits year after year. In this eagerly awaited new edition, Charles D. Ellis applies the expertise he has developed over half a century working with the world's leading investment experts. This updated edition includes: NEW CHAPTERS on bond investing, how investor behavior affects returns, and how technology and big data are challenging traditional investment decisions NEW RESEARCH and evidence supporting the case for indexing operations NEW INSIGHTS into the role of governance, developing a comprehensive saving strategy, and the power of regression to the mean With Winning the Loser's Game, you have everything you need to identify your unique investment objectives, develop a realistic and powerful investment program, and drive superior results"--
Includes bibliographical references and index.
Keywords: Portfolio management; Investments; Investment analysis